Body: an ambiguous sort of being. Approach toward philosophy of body in Merleau-Ponty’s phenomenology (2011)
This work is an approximation to the philosophy of body starting from Maurice Merleau-Ponty’s Phenomenology of Perception -- Based on the concept of phenomenal body, we find a conception of body depicted as an ambiguous sort of being -- The following sections are developed: the bodily experience: perception and object, the phenomenal body and the experience of space, temporality: retention and propensity, being-in-the-world and body as expressive space -- So, from the experience of the own’s body and against the idea of a subject who owns himself through self-understanding, it is shown how the boundaries between subject and object, activity and passivity, interiority and exteriority or spirit and nature vanish in the ambiguity of the body and the existence